DIGITAL ASSESSMENT MANAGEMENT IN QUALITY ASSURANCE OF ISLAMIC EDUCATION LEARNING OUTCOMES AT MAN 18 JAKARTA - Masitoh Masitoh (Jurnal Kajian Pendidikan dan Psikologi, 2026)
Digital transformation in education requires madrasahs to develop an assessment system that is not only effective in measuring learning outcomes but also capable of supporting the continuous quality assurance of learning outcomes. This study aims to analyze the management of digital-based learning assessments in the subject of Islamic Religious Education (PAI) and its contribution to the Internal Quality Assurance System (SPMI) at MAN 18 Jakarta. The study employs a qualitative approach using a descriptive-analytical method. Informants were selected through purposive sampling, including the madrasah principal, the vice principal for curriculum, the Madrasah Education Quality Assurance Team (TPMPS), PAI teachers, and students. Data were collected through in-depth interviews, participatory observation, and analysis of documentation such as teaching modules, assessment instruments, rubrics, and digital learning outcome data. Data validity was strengthened through triangulation of sources and methods, while data analysis utilized the interactive model proposed by Miles, Huberman, and Saldaña. The research findings indicate that digital assessment management occurs through four main processes: planning assessment instruments aligned with learning outcomes; conducting assessments via digital platforms; utilizing analytical data on learning outcomes; and quality control and improvement through the PPEPP cycle. Assessment data is used to identify learning mastery, design remedial and enrichment programs, evaluate the quality of assessment instruments, and recalibrate teachers’ instructional strategies. Challenges such as varying levels of digital literacy, connectivity issues, and infrastructure limitations are addressed through ongoing training and contingency procedures. The study concludes that digital assessment management can serve as a strategic tool for fostering data-driven decision-making and sustainably improving the quality of Islamic Religious Education (IRE) learning outcomes.